Biopolymer-Based Hybrids as Effective Admixtures for Cement Composites - Ślosarczyk, Agnieszka (Polymers (Basel), 2020)
In the framework of this publication, silica-lignin hybrid materials were designed, obtained, characterized and then used as admixtures for cement composites. High-energy mechanical grinding of individual components was used to produce the systems that allowed ensuring adequate homogeneity of the final products. As a result of the analysis of Fourier transform infrared spectroscopy, it has been confirmed that weak physical interactions occur between the components. This allowed classifying the resulting systems as I class hybrid materials. In addition, the efficiency of obtaining final products was also inferred on the basis of obtained porous structure parameters and colorimetric data. The achieved bio-admixture with different weight ratios of silica and lignin was added to cement pastes in the amount ranging from 0.5 to 1 wt.%. The study showed that increasing the ratio of lignin in the admixture from 0.15 to 1 wt.% had a positive effect on the rheological properties of the pastes, while the mechanical properties of the composite were deteriorated. In turn, a higher amount of silica in the admixture acted in reverse. The most favorable results were obtained for a silica-lignin bio-admixture with a weight ratio of components equal to 5:1 wt./wt. A significant increase in compressive strength was gained at satisfactory plasticity of the paste.